Additional BCAA-enriched nutrient mixture improves the nutritional condition in cirrhotic patients with hypoalbuminemia despite treatment with regular BCAA granules: A pilot study - Fukui, Aiko; Kawabe, Naoto; Hashimoto, Senju; Murao, Michihito; Nakano, Takuji; Shimazaki, Hiroaki; Kan, Toshiki; Nakaoka, Kazunori; Ohki, Masashi; Takagawa, Yuka; et al. (Turkish Journal of Gastroenterology, 2015)
Abstract Background/Aims: To elucidate the effect of adding branched-chain amino acid (BCAA)-enriched nutrient mixtures in cirrhotic patients with hypoalbuminemia despite the use of BCAA granules. Materials and Methods: A BCAA-enriched nutrient mixture containing 5.6 g of BCAA and 210 kcal was additionally administered in 40 cirrhotic patients with hypoalbuminemia despite their treatment with BCAA granules containing 12 g of BCAA. Laboratory data were assessed at 6 months before beginning additional therapy, at baseline, and at 6 months after baseline. Results: Serum albumin levels significantly decreased from 6 months before baseline (3.14±0.47 g/dL) to baseline (2.83±0.46 g/dL), despite the treatment with BCAA granules (p<0.001), and tended to increase from baseline to 6 months after baseline (2.95±0.42 g/dL) (p=0.084). In the subset of 23 patients without hepatocellular carcinoma treatments, upper gastrointestinal tract bleeding, or albumin infusion, serum albumin levels significantly increased from baseline (2.93±0.38 g/dL) to 6 months after baseline (3.15±0.34 g/dL) (p=0.014). Conclusion: Additional therapy with BCAA-enriched nutrient mixtures increased serum albumin levels of the cirrhotic patients with hypoalbuminemia despite the treatment with BCAA granules and without hepatocellular carcinoma treatment, upper gastrointestinal tract bleeding, or albumin infusion.